Cell-type-specific molecular characterization of cells from circulation and kidney in IgA nephropathy with nephrotic syndrome - Chen, Qilin; Jiang, Huimin; Ding, Rong; Zhong, Jinjie; Li, Longfei; Wan, Junli; Feng, Xiaoqian; Peng, Liping; Yang, Xia; Chen, Han; Wang, Anshuo; Jiao, Jia; et al. (Frontiers in Immunology, 2023)
Nephrotic syndrome (NS) is a relatively rare and serious presentation of IgA nephropathy (IgAN) (NS-IgAN). Previous research has suggested that the pathogenesis of NS-IgAN may involve circulating immune imbalance and kidney injury; however, this has yet to be fully elucidated. To investigate the cellular and molecular status of NS-IgAN, we performed single-cell RNA sequencing (scRNA-seq) of peripheral blood mononuclear cells (PBMCs) and kidney cells from pediatric patients diagnosed with NS-IgAN by renal biopsy. Consistently, the proportion of intermediate monocytes (IMs) in NS-IgAN patients was higher than healthy controls; furthermore, flow cytometry confirmed that IMs were significantly increased in in pediatric patients with NS. The characteristic expression of VSIG4 and MHC class II molecules and an increase in oxidative phosphorylation may be important features of IMs in NS-IgAN. Notably, we found that the expression level of CCR2 was significantly increased in CMs, IMs, and NCMs of patients with NS-IgAN; this may be related to kidney injury. Regulatory T cells (Tregs) are classified into two subsets of cells: Treg1 (CCR7high, TCF7high, and HLA-DRlow) and Treg2 (CCR7low, TCF7low, and HLA-DRhigh). We found that the levels of Treg2 cells expressed significant levels of CCR4 and GATA3; this may be related to the recovery of kidney injury. The state of NS in patients was closely related to podocyte injury. The expression levels of CCL2, PRSS23, and genes related to epithelial-mesenchymal transition were significantly increased in podocytes from NS-IgAN patients; these represent key features of podocyte injury. Our analysis suggests that PTGDS is significantly downregulated following injury and may represent a new marker for podocytes. In this study, we systematically analyzed molecular events in the circulatory system and kidney tissue of pediatric patients with NS-IgAN, which providing new insights for targeted therapy in future.